2014
DOI: 10.4155/bio.13.289
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous LC–MS/MS Quantification of P-Glycoprotein and Cytochrome P450 Probe Substrates and Their Metabolites in DBS and Plasma

Abstract: Due to its low-invasiveness, simple sample collection and minimal sample preparation, DBS represents a suitable method to simultaneously monitor in vivo activities of P-gp and CYP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(76 citation statements)
references
References 32 publications
5
71
0
Order By: Relevance
“…In contrast to Donzelli et al, the higher volume, combined with the use of more sensitive equipment, allowed quantification of all probe drugs and corresponding metabolites in DBS. Single point metabolite/parent drug ratios at 2 h for CYP1A2 and CYP3A4 and at 3 h for CYP2B6, CYP2C9 and CYP2D6, and the AUC 2,3,6 metabolite/parent drug ratio for CYP2C19 showed acceptable Spearman rank correlation coefficients with AUC last ratios in plasma, both when the cocktail was administered alone or in combination with CYP450 inhibitor and inducer drugs [43,44].…”
Section: Dried Blood Spotsmentioning
confidence: 94%
“…In contrast to Donzelli et al, the higher volume, combined with the use of more sensitive equipment, allowed quantification of all probe drugs and corresponding metabolites in DBS. Single point metabolite/parent drug ratios at 2 h for CYP1A2 and CYP3A4 and at 3 h for CYP2B6, CYP2C9 and CYP2D6, and the AUC 2,3,6 metabolite/parent drug ratio for CYP2C19 showed acceptable Spearman rank correlation coefficients with AUC last ratios in plasma, both when the cocktail was administered alone or in combination with CYP450 inhibitor and inducer drugs [43,44].…”
Section: Dried Blood Spotsmentioning
confidence: 94%
“…In this study, which is the largest published DBS-based phenotyping study to date, caffeine and its main metabolite paraxanthine were determined in capillary DBS, venous DBS, whole blood and plasma in the context of CYP1A2 phenotyping. Although a proof-of-principle of DBS-based CYP phenotyping is already available [20][21][22][23][24], all published studies had small data sets (n  16) and did not include a systematic evaluation of DBS-specific parameters. Moreover, with a single exception [23], all studies started from volumetrically applied DBS, an approach that is difficult to sustain when envisaging patient self-sampling at home.…”
Section: Discussionmentioning
confidence: 99%
“…Although we and others [20][21][22][23][24] demonstrated that DBS can be used for phenotyping CYP enzymes, no report has evaluated the impact of variation of these parameters on the phenotyping index. First, we did not observe significant differences between caffeine and paraxanthine concentrations measured in discs punched out peripherally versus centrally, irrespective of the Hct (Supplementary Figure S7).…”
Section: Dbs-specific Parametersmentioning
confidence: 99%
See 2 more Smart Citations